ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE DENGAN LEVERAGE SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan Food and Beverage Stock Exchange of Thailand Periode Tahun 2015-2019 ) - Arofatul Jannah; Muhaimin Dimyati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2021)
This study aims to analyze Company Size, Institutional Ownership, Executive Character, Sales Growth, and Profitability against Tax Avoidance with leverage as an intervening variable. The data used are financial reports (annual reports) during 2015 - 2019. The sample method used in this study is purposive sampling. The entire sample consists of 10 food and beverage companies listed on the Thailand Stock Exchange. The analysis tool used was SPSS 23.0. Hypothesis testing is using Path Analysis and Sobel Test. The results showed that Institutional Ownership (X2), Executive Character (X3) and Sales Growth (X4), showed a direct influence on Leverage (Z). Meanwhile, the variable Company Size (X1) and Profitability (X5) shows an indirect effect on Leverage (Z). Company Size (X1) and Leverage (Z) show a direct effect on Tax Avoidance (Y). Meanwhile, the variables of Institutional Ownership (X2), Executive Character (X3), Sales Growth (X4), and Profitability (X5) show an indirect effect on Tax Avoidance (Y). Based on the Sobel Leverage (Z) test, it is unable to become an intervening variable between Company Size (X1), Institutional Ownership (X2), Executive Character (X3), Sales Growth (X4), and Profitability (X5) on Tax Avoidance (Y).